Hyperuricemia and Gout – Ins and Out - Razzak, Md Abdur; Rahman, Quazi Audry Arafat; Nasreen, Fahtiha (Journal of Armed Forces Medical College, Bangladesh, 2020)
Gout is a condition characterized by the deposition of monosodium urate crystals in the joints or soft tissue. The four phases of gout include asymptomatic hyperuricemia, acute gouty arthritis, intercritical gout and chronic tophaceous gout. The peak incidence occurs in patients 30 to 50 years old, and the condition is much more common in men than in women. Patients with asymptomatic hyperuricemia do not require treatment, but efforts should be made to lower their urate levels by encouraging them to make changes in diet or lifestyle. Acute gout most commonly affects the first metatarsal joint of the foot, but other joints are also commonly involved. Definitive diagnosis requires joint aspiration with demonstration of birefringent crystals in the synovial fluid under a polarized light microscope. Treatment includes nonsteroidal anti-inflammatory drugs (NSAIDs), colchicine, corticosteroids and analgesics. In patients without complications, NSAID therapy is preferred. JAFMC Bangladesh. Vol 15, No 2 (December) 2019: 227-234